Is there any difference in fitness profiles among the Croatian basketball players? : position specific analysis - Milanović, Luka (Array, 2019)
The aim of the study was to establish possible differences in both aerobic and anaerobic fitness parameters among different positions (point guards, guards and small forwards, and power forwards and centers) in basketball. Based on previous research on certain differences among play positions in basketball, aerobic and anaerobic fitness capacity values of basketballers in different positions were analyzed. Seventy adult basketball players (age 24.37±4.05 years) from the Croatian Division 1 league were classified as point guards (n=20), shooting guards and small forwards (n=26), and power forwards and centers (n=24). Six variables of cardiopulmonary function were obtained using spirometry and spiroergometry test. Regarding aerobic abilities, a significant difference among the three positions was found only in the VO2max parameters (p=.00) in favor of power forwards and centers (5.55± 0.6 l/min) when compared to point guards (4.7± 0.6 l/min) and shooting guards and small forwards (5.01±0.6 l/min). No significant difference was found in the Croatian basketballers’ anaerobic capacity parameters among the three different play positions.